2003
DOI: 10.1159/000070757
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Serological Markers of Hepatitis B and C Viruses in Istanbul, Turkey

Abstract: Objective: This study was undertaken to investigate the prevalence of HBsAg, anti-HBs and anti-HCV positivity in Istanbul, Turkey. Subjects and Methods: The frequencies of HBsAg, anti-HBs and anti-HCV positivity were determined in 1,157 randomly selected patients attending the outpatient clinic of Istanbul University Hospital, Istanbul, Turkey, during the years 1998 and 2001. All patients underwent complete physical and various routine laboratory examinations. Results: Of the 1,157 patients, the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
4
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 8 publications
3
19
4
3
Order By: Relevance
“…A study from Turkey reported the prevalence of anti-HCV was 2.4% as compared to 14% -16% in our study which is significantly higher [32]. The results of international studies are not comparable to our local results especially in case of HCV, reason being more awareness and better preventive measures, in developed countries.…”
Section: Discussioncontrasting
confidence: 97%
“…A study from Turkey reported the prevalence of anti-HCV was 2.4% as compared to 14% -16% in our study which is significantly higher [32]. The results of international studies are not comparable to our local results especially in case of HCV, reason being more awareness and better preventive measures, in developed countries.…”
Section: Discussioncontrasting
confidence: 97%
“…In this study, the frequency of HBV and HCV infections were lower compared to reports from surrounding countries in the region e.g. Iran and Turkey, [15,16] whereas the prevalence of HBV was higher than some countries, e.g. Switzerland.…”
Section: Discussioncontrasting
confidence: 58%
“…In a past epidemiological study, anti-HCV was detected in 21 (1.5%) of 1,374 persons and was more common in residents over 54 years of age in Turkey [14]. Data from past studies on the risk factors for HCV infections in Turkey revealed that a prior history of blood transfusion and nosocomial risk factors accounted for the majority of HCV cases, while IVDU was reported in a small number of HCV cases (4% or less) [13,16,26,27]. Likewise sexual transmission and mother-to-child transmission was low in Turkey [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Since most of the studies on the epidemiology of HBV and HCV infections in Turkey were conducted in blood donors and risk groups and limited nation-wide data are available in the general population [7,8,12,[15][16][17][18][19], the present population-based, large scale field study was designed to determine seroprevalence of hepatitis B, Delta and C virus infections in relation to risk factors for increased seropositivity in Turkish general population.…”
Section: Introductionmentioning
confidence: 99%